The Impact of Brand Awareness on Customer Loyalty in Selected Food and Beverage Businesses in Lagos State Nigeria - Adeyemi Omolade Sunday; Olubiyi Timilehin Olasoji (Jurnal Multidisiplin Madani, 2023)
The pursuit of competitive advantage and increase in customer brand loyalty post-pandemic have compelled businesses to be strategic, particularly regarding brand awareness decisions. However, shaping brand management, increasing brand awareness development and adaptation which are critical activities in modern marketing has been an issue in developing nations like Nigeria. The purpose of this study is to examine effect of brand awareness on customer-loyalty in the food and beverage industry in Lagos State, Nigeria. This study used survey research design facilitated through a structured research instrument. Using quantitative method six hundred respondents from the selected food and beverage companies in Lagos state participated and data was collected using questionnaire. A total of 600 copies of questionnaire were administered to the respondents with a response rate of 100.00%. The collected data was analyzed and presented both in descriptive and inferential analysis. The findings of this study revealed that brand awareness have significant positive effect on customer loyalty. Based on the findings of this study it is concluded that brand awareness (brand impression, brand competence, and brand value) are a strategic tool for achieving customer loyalty in food and beverage industry in Lagos state, Nigeria and that  brand awareness has significant effect on customer loyalty in food and beverage industry in Lagos state, Nigeria. Hence, this study recommends that the food and beverage industries in Lagos state, Nigeria should apply brand impression, competence, management and value in order to maintain customer brand loyalty and competitive advantage